Is adjunctive naturopathy associated with improved glycaemic control and a reduction in need for medications among type 2 Diabetes patients? A prospective cohort study from India. Issue 1 (December 2016) - Bairy, Srinivas; Kumar, Ajay; Raju, MSN; Achanta, Shanta; Naik, Balaji; Tripathy, Jaya; Zachariah, Rony
Abstract Background With an estimated 65 million Diabetes Mellitus (DM) patients, India ranks second in the world in terms of DM burden. The emphasis of current medical practice has been on pharmacotherapy but, despite the best combination therapies, acheiving glycaemic control (reduction of blood sugar to desirable levels) is a challenge. 'Integrated Naturopathy and Yoga'(INY) is an alternative system of medicine that lays emphasis on the role of diet and physical exercise. We assessed the short term effect of INY as an adjunct to pharmacotherapy on glycaemic control among type 2 DM patients. Methods In this prospective cohort study with a 3 month follow-up, DM patients consecutively admitted to a hospital in India from May-October 2014 for either 15 or 30 days were offered INY - a package of vegetarian diet with no added oil, sugar and salt, yoga-based exercise, patient counselling and rest. A 'favourable outcome' was defined as glycaemic control (glycosylated hemoglobin (HbA1c ) < 7 % or absolute reduction by 1 %) along with at least 50 % reduction in antidiabetes medication at 3 months relative to baseline. Compliance to diet was scored by self-report on a scale of 0–10 and categorized into poor (0–5), moderate (6–8) and excellent (9–10). Results Of 101 patients with 3-month follow-up data, 65(65 %) achieved a favourable outcome – with 19(19 %) stopping medication while sustaining glycemic control. Factors associated with favourable outcome were baseline HbA1c and compliance to diet, which showed a significant linear relationship with mean HbA1c reductions of 0.4 %, 1.1 % and 1.7 % in relation to poor, moderate and excellent dietary compliance respectively. Conclusion INY, adjunctive to pharmacotherapy, was associated with a significant beneficial effect on glycaemic control and reduced the overall need for antidiabetes medications. These early results are promising. Further studies with long-term follow-up and using more rigorous randomized controlled trial designs are needed.